Effect of Withering and Drying Process of Cemara Udang (Casuarina equisetifolia) Leaves to Functional Herbal Tea - Handarini, Kejora; Rahmiati, Retnani; Yuniati, Yuyun (agriTECH, 2025)
The industry is intensively producing health product from herbal plants to combat free radicals and prevent the potential of cancer disease in the body. In Indonesia, Cemara Udang (Casuarina equisetifolia) leaves have been investigated as herbal tea product for antioxidant purposes as a free radical scavenger from various plants. This herbal tea requires significant attention during processing to produce a quality final product. Therefore, this research aimed to examine the effect of setting withering times of 14 and 16 hours, along with a drying temperature of 40 and 50 °C on cemara udang leaves. Product quality was evaluated based on the chemical components and nutritional characteristics of tea, such as moisture content, pH, antioxidant activity, total phenolic content, and vitamin C, as well as sensory aspects. The evaluation was carried out based on the degree of preference for color, aroma, and taste. Fresh cemara udang samples had 46.57% moisture content, pH 7.05, 131.53 µg/mL IC50 value, 1.53 mg/100 g total phenolic, and 43.46% vitamin C. Based on the degree of preference, color, flavor, and taste hedonic score had 3.11, 2.57, and 1.94 out of 7.00, respectively. Tea of cemara udang that was withered for 16 hours and dried at 50°C showed good quality stability with favorable sensory attributes. This varies significantly compared to the control, with 10.32% moisture content, pH 7.04, 137.94 µg/mL IC50 value, 1.2 mg/100 g total phenolic, and 29.26% vitamin C. Furthermore, color, flavor, and taste hedonic scores had 6.37, 6.03, and 6.27 out of 7.00, respectively.